Anterior Cruciate Ligament Hybrid Remnant Preservation Reconstruction Demonstrates Equivalent Patient-Reported Outcomes and Complications as Traditional Anterior Cruciate Ligament Reconstruction After 1 Year - Vasilios Moutzouros, M.D; Joshua P. Castle, M.D; Matthew A. Gasparro, B.S; Eleftherios L. Halkias, B.S; Justin Bennie, B.S (Elsevier, 2024)
Purpose: To compare the outcomes of anterior cruciate ligament (ACL) Hybrid Remnant Preservation Reconstruction (HRPR) with traditional anterior cruciate ligament reconstruction (ACLR) and determine differences in patient-reported outcomes, range of motion (ROM), and complications after 12 months. Methods: A retrospective cohort study of patients undergoing ACLR by a single surgeon from December 2020 to January 2022 was conducted. Patients undergoing ACL-HRPR were compared with control patients undergoing traditional ACLR with bone−patellar tendon−bone autograft. Preoperative and postoperative Patient-Reported Outcome Measurement Information System scores, International Knee Documentation Committee, and patient acceptable symptom state were recorded over 12 months. Any complications occurring 12 months postoperatively were collected. Results: The final analysis included 104 patients, with 39 undergoing ACL-HRPR compared with 65 ACLR controls. Patients who received HRPR were on average 19.46 ± 5.01 years old, with 51.28% being female, whereas control patients were, on average, 21.92 ± 7.71 years old with 50.77% being female. Total ROM was equivalent between groups, with complete terminal extension at 12 months. No significant differences were found for patient acceptable symptom state; Patient-Reported Outcome Measurement Information System-Physical Function, -Pain Interference, or -Depression; or International Knee Documentation Committee at 6 months and 12 months postoperatively. Total ROM was similar between the HRPR and control groups. No differences were found for timed 6-meter hop test, hop for distance, or KT-1000 side-to-side differences. Over the 12-month period, complication rates were similar between groups (10% vs 12% P = .75) were similar. Conclusions: ACL HRPR is associated with equivalent patient-reported outcomes, full ROM, and no differences in complications rates after 1 year compared with control patients in the present retrospective study. Level of Evidence: Level III, retrospective cohort study.